Prevalence of Vitamin- D Deficiency among Women with Gestational Diabetes Mellitus - Habiba Sharaf Ali; Quratul Ain Zahid (Journal of Bahria University Medical and Dental College)
Objective: To determine the frequency of vitamin D3 deficiency among women with Gestational Diabetes mellitus visiting tertiary care hospital. Materials and Methods:This descriptive case series study was carried out in Obstetrics and Gynecology department at Dr. Ziauddin Hospital Karachi for a period of six months. 136 GDM women with age 18 to 30 years having singleton pregnancy and gestational age of 24-40 weeks were enrolled. Patients were offered according to ADA (American Diabetic Association) recommendations, 1 hour 50gm Oral Glucose Challenge Test, without any preparation or fasting. Then 1 hour later plasma glucose measurements were done. If values were>140 mg/dl or 7.8m.mol/l then 3 sample 75g Oral Glucose Tolerance Test (WHO criteria) was offered (to diagnose GDM) on next visit. The mothers were advised not to have breakfast on the day of the diagnostic test.Then fasting blood glucose sample was taken. Afterwards hourly samples were taken till 2 hours. If one reading was raised then diagnosis was established as impaired glucose intolerance and if two readings were raised then diagnosis was confirmed as gestational diabetes mellitus. Estimation of vitamin D levels by Electrochemilumenscence technique was done in diagnosed GDM women. Results: Mean age of the patients was 26.46 ±2.91 years. Mean gestational age of the patients was 33.03 ±6.14weeks. There were 57 (41.90%) primiparous and 79 (58.1%) multiparous patients. Frequency of vitamin D deficiency was found in 84 (61.80%) patients with GDM. Conclusion: The frequency of vitamin D3 deficiency was found higher among women with GDM visiting tertiary care hospital.